The Effect of Cold Compresses On Reducing The Intensity of Postpartum Perineal Pain In PMB of The Sungai Langkai Public Health Center, Batam City in 2024 - Windayani Windayani; Renny Adelia Tarigan; Roza Erda (Journal of Midwifery and Nursing, 2026)
Perineal pain occurs due to perineal rupture either spontaneously or episiotomy during the labor process. The feeling of pain will appear when an injury occurs. The perineal pain that is not treated properly will cause the postpartum complications, such as infection and bleeding during postpartum. As indicated by the results of the 2023 Indonesian Health Survey, there are 42.7% of postpartum hemorrhage cases and there are 25.9% of postpartum infections. Cold compresses are one of the alternative nonpharmacological methods to treat perineal pain. The aims of the research is going to analyze In 2024, the Sungai Langkai Community Health Centre in Batam City conducted research on the effect of cold compresses on reducing the intensity of postpartum perineal pain in mothers who had given birth. For this study, a pre-experimental design was used, and a pre-test and post-test group were designed. The sample of this research was 15 postpartum mothers with perineal tears. The results showed that the respondents' perineal pain was severe before the intervention was carried out was an average of 5.73 average intensity of perineal pain after intervention was 1.33. Based on the results of the Paired Sample T-test statistical test, a significance value of 0.000 was obtained, which is smaller than the significance level of 5% (p-value = 0.000 < 0.05). Therefore, it can be concluded that cold compresses help reduce the intensity of perineal pain experienced by mothers after delivery with PMB Sungai Langkai Public Health Center, Batam City in 2024. It is recommended for Midwifery to provide cold compress therapy in providing care for mothers who have just given birth and are experiencing pain in the perineal area